الخط المغربي: تاريخه وأنواعه وخصائصه - أ. فاطمة طاهري; أ. أنس بوسلام (Journal of Calligraphy, 2021)
The article deals with the history and spread of Al khatt al maghribi. this khatt which descends from Al khatt al koufi. The article then reviews the types of Al khatt al maghribi, the most prominent of which are: - Al khatt al koufi al maghribi - Al khatt al Mabsout - Al khatt al moujawhar - khatt A-thuluth - Al khatt al Musnad or Al khatt al Zamami. Finally, the article explains the most prominent characteristics of Al khatt al maghribi, such as the absence of specific rules. تاريخ الخط المغربي وانتشاره، هذا الخط الذي ينحدر من الخط الكوفي بالمشرق. ثم يستعرض المقال أنواع الخط المغربي وأبرزها: - الخط الكوفي المغربي- الخط المبسوط – الخط المجوهر – خط الثلث المغربي، - خط المسند أو الزمامي، وفي الأخير يوضح المقال أبرز خصائص الخط المغربي كعدم وجود قواعد محددة لهذا الخط.